PENGAJARAN KITAB-KITAB FIQIH DI PESANTREN - Husen Hasan Basri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractIn addition to clerics and values, yellow books are essential elements of an Islamic boarding school. Yellow Books are Islamic boarding school instructional materials that have been used for a long time. One area of yellow book that has been long taught is jurisprudence (fiqh) field. Teaching of fiqh books starts from the low level books, such as Safinahan-Najah to the high level books, such as Al-Muhadzdzab. Teaching methods used were Bandongan and Sorogan methods. In line with diversified development of forms and types of education in Islamic boarding schools, such as formal education (madrassas and schools) and vocational education, it is expected that teaching of yellow books, including books of fiqh, was changing, either books taught, teaching methods used, number of meetings in teaching, and teaching level. Through a survey of 951 schools in 15 provinces of 72 books of fiqh chosen by the researchers, there were 5 books of 72 books of fiqh included in a group of the most widely taught books of fiqh, namely: Taqrib, Safinah an-Najah, Fath al-Mu’in, Fath al-Qarib, and Sullam at-Taufiq. Besides Fath al-Mu’in, these books are elementary books of fiqh.AbstrakSelain Kyai dan tata nilai, kitab kuning merupakan unsur pokok dari sebuah pondok pesantren. Kitab kuning adalah bahan ajar pesantren yang sudah lama digunakan. Salah satu bidang kitab kuning yang sudah lama diajarkan adalah bidang fiqih. Pengajaran kitab-kitab fiqih dimulai dari kitab tingkat rendah seperti kitab Safinah an-Najah sampai kitab tinggi seperti kitab al-Muhadzdzab. Metode pengajarannya menggunakan metode bandongan dan sorogan. Seiring dengan munculnya diversifikasi pengembangan bentuk dan jenis-jenis Pendidikan di pesantren seperti Pendidikan formal (madrasah dan sekolah) dan Pendidikan keterampilan, diduga pengajaran kitab kuning, termasuk kitab-kitab fiqih, mengalami perubahan pengajaran kitab, baik kitab-kitab yang diajarkan, metode pengajaran yang digunakan, jumlah pertemuan dalam pengajaran, dan tingkat pengajaran. Melalui survei pada 951 pesantren di 15 propinsi terhadap 72 kitab fiqih hasil pilihan peneliti, terdapat 5 kitab dari 72 kitab fiqih yang termasuk kelompok kitab fiqih yang banyak diajarkan, yaitu: Taqrib, Safinah an-Najah, Fath al-Mu’in, Fath al-Qarib, dan Sullam at-Taufiq. Kecuali, Fath al-Mu’in, kitab-kitab tersebut merupakan kitab-kitab fiqih elementer.